Defining compassionate nursing care. (March 2020) - Su, Jing Jing; Masika, Golden Mwakibo; Paguio, Jenniffer Torralba; Redding, Sharon R
Background: Compassion has long been advocated as a fundamental element in nursing practice and education. However, defining and translating compassion into caring practice by nursing students who are new to the clinical practice environment as part of their educational journey remain unclear. Objectives: The aim of this study was to explore how Chinese baccalaureate nursing students define and characterize compassionate care as they participate in their clinical practice. Methods: A descriptive qualitative study design was used involving a semi-structured in-depth interview method and qualitative content analysis. Twenty senior year baccalaureate nursing students were interviewed during their clinical practicum experience at four teaching hospitals. Ethical considerations: Permission to conduct the study was received from the Institutional Review Boards and the participating hospitals. Results: Baccalaureate nursing students defined and characterized compassionate care as a union of "empathy" related to a nurse's desire to "alleviate patients' suffering, " "address individualized care needs, " "use therapeutic communication, " and "promote mutual benefits with patients." Students recognized that the "practice environment" was characterized by nurse leaders' interpersonal relations, role modeling by nurses and workloads which influenced the practice of compassionate care by nursing personnel. Conclusion: Compassionate care is crucial for patients, nurses, and students in their professional development as well as the development of the nursing profession. In order to provide compassionate care, a positive practice environment promoted by hospital administrators is needed. This also includes having an adequate workforce of nurses who can role model compassionate care to students in their preceptor role while meeting the needs of their patients.